Cost-effectiveness analysis of serological prenatal screening for pregnant women in King Abdulaziz University Hospital: a single-center retrospective study - Saeed Asiri, Atheer Yahya; Alsawa, Ibtisam Talak Audallah; Fallatah, Anas Mahmoud Omar; Hussein, Sondos Sami; Alshehri, Hisham Z.; Aljahdali, Aseel Ahmed Mohammedali; Fatani, Arwa Zuhair; Albasri, Samera (International Journal Of Community Medicine And Public Health, 2019)
Background: Congenital primary infections with Toxoplasma gondii, cytomegalovirus (CMV), Epstein–Bar virus (EBV), rubella, and hepatitis B virus (HBV) are viral infections transmitted transplacentally through the blood to the fetus and can be life-threatening. Therefore, we aimed to determine the prevalence of these infections and assess the cost-effectiveness of blood tests among pregnant women with positive serologies. Methods: This retrospective review was conducted among pregnant women with positive prenatal screening serology test results between January 2013 to July 2018. A p-value of <0.05 was used to calculate statistical significance. Results: Overall, 9095 pregnant women delivered in the last 5 years. Of these, 97 had positive prenatal screening serology and were enrolled in our study. Of 97, 61 (62.9%) were Saudis and 36 (37.1%) non-Saudis. The prevalence rates of rubella, CMV, EBV, and HBV were 78.35%, 59.79%, 14.43%, and 5.15%, respectively. Additionally, 44 of 97 women developed undesired antepartum outcomes, whereas 47 had adverse neonatal outcomes. CMV, HBV, and rubella were significantly associated with adverse pregnancy outcomes (P<0.005). During the study period, USD 1460228.27 was spent to screen 9095 pregnant women and USD 15573.68 to diagnose 97 pregnant women with positive serology. Conclusions: Because infections with toxoplasma, CMV, EBV, rubella, and HBV can cause serious risk to the mother and fetus during pregnancy. Thus, setting new hospital policies regarding early screening for high-risk pregnancies and early detection of these infections during prenatal visits are inevitable to avoid undesired outcomes.